PENGEMBANGAN MEDIA ACROSS SMART PADA MATERI BILANGAN BULAT UNTUK SISWA KELAS IV SD MUHAMMADIYAH NGUPASAN 2 YOGYAKARTA - Saputro, Hengkang Bara; Sari, Vera Fadhela (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2023)
The aim of this research is to determine the steps for developing Across Smart mathematics media and determine the feasibility of learning media Across Smart mathematics with integer material for fourth grade elementary school students. The research method used is research and development with the borg and gall model. The small group trial was carried out at SD N Muhammadiyah Ngupasan 2 Yogyakarta with a total of 23 students. The data analysis techniques of this research are qualitative data and quantitative data. The qualitative data in this research is in the form of criticism and suggestions from material experts, learning evaluation experts, teachers and students. The quantitative data in this research is in the form of expert, teacher and student assessments. Based on the research results, assessment data was obtained from material experts with an average score of 92.7